PENGARUH INFLUENCER MARKETING DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT PADA MAHASISWI PRODI MANAJEMEN UNIVERSITAS MUHAMMADIYAH BENGKULU - Erviana, Della; Ekowati, Sri (UM. Bengkulu, 2024)
This research aims to determine the influence of influencer marketing and brand awareness on purchasing decisions for scarlett products among management study program students at Muhammadiyah university of Bengkulu either partially or simultaneously. There are several factors that will be discussed in this research including influencer marketing and brand awareness. The object of this research was management students from muhammadiyah university of Bengkulu, totaling 102 people. In this research the author used data collection methods by ibservation and distributing questionnaires. Data analysis techniques in this research use instrument testing, multiple linier regression analysis, hypothesis testing and coefficient of determination analysis. The result show that influencer marketing has a positive effect on purchasing decisions, then brand awareness has a positive affect on purchasing decisions. So, from the results of the research that has been conducted, it can be concluded that influencer marketing and brand awareness have a partial or simultaneous influence on Scarlett purchasing decisions among management study program students at Muhammadiyah university of Bengkulu. Keywords : influencer marketing, brand awareness and purchasing decisions.